DIAGNÓSTICO DE DUAS TRAJETÓRIAS PRODUTIVOS DISTINTOS – A AGROECOLOGIA E A AGRICULTURA CONVENCIONAL Suas perspectivas para o desenvolvimento rural de São Mateus do Sul - PR - Okonoski, Thales Ravel Hetka (2012)
This study sought to understand two representative productive segments of the rural areas of São Mateus do Sul - PR, characterized by conventional farmers guided by the production of tobacco, and agro ecological horticultural producers and also to analyze their perspectives into the rural development. So, this discussion was contextualized around the rural development, analyzing concepts and development processes applied in Latin America and Brazil and the current discussion on territorial development. Inside a case study, performed a qualitative survey through field observations, analysis of public politics and interviews with familiar farmers participating in the productive segments concerned, assessing their productive viability and their representativeness in the municipal rural development and territorial rural development too.